Short communication: Enhanced enrichment is inevitable to carry on the legacy of African civet (Civettictis civetta) captive farming - TAKELE TAYE DESTA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Desta TT. 2019. Enhanced enrichment is inevitable to carry on the legacy of African civet (Civettictis civetta) captive farming. Biodiversitas 20: 1575-1579. African civet secrets an aromatic compound called civet musk. Ethiopia has a long-lasting production and trading history of civet musk. Ethiopia holds about 90% of the international market share. Irrespective of economic importance and histocultural significance; inadequate enrichment and suboptimal management have been increasingly threatened the welfare of captive civets. To carry on with the legacy of captive civet farming, current management practice should have to be improved and additional civet and civet musk derived use values should have to be sought after.